2022
DOI: 10.1155/2022/6345404
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Consumption and Traffic Emissions Evaluation of Mixed Traffic Flow with Connected Automated Vehicles at Multiple Traffic Scenarios

Abstract: To analyze the impact of different proportions of connected automated vehicles (CAVs) on fuel consumption and traffic emissions, this paper studies fuel consumption and traffic emissions of mixed traffic flow with CAVs at different traffic scenarios. Firstly, the car-following modes and proportional relationship of vehicles in the mixed traffic flow are analyzed. On this basis, different car-following models are applied to capture the corresponding car-following modes. Then, Virginia Tech microscopic (VT-micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…The speed planning algorithm, based on the Krauss car-following model [31], is simulated and verified. The resulting trajectories and speeds of both the Krauss and Model Predictive Control (MPC) following vehicles [32] are illustrated in Figure 18 and Figure 19, respectively. Notably, the plug-in hybrid ECVT demonstrates the ability to navigate each signal intersection effectively while also achieving a superior tracking performance relative to the pure electric vehicle (EV).…”
Section: Case Study and Discussionmentioning
confidence: 99%
“…The speed planning algorithm, based on the Krauss car-following model [31], is simulated and verified. The resulting trajectories and speeds of both the Krauss and Model Predictive Control (MPC) following vehicles [32] are illustrated in Figure 18 and Figure 19, respectively. Notably, the plug-in hybrid ECVT demonstrates the ability to navigate each signal intersection effectively while also achieving a superior tracking performance relative to the pure electric vehicle (EV).…”
Section: Case Study and Discussionmentioning
confidence: 99%
“…with the rapid increase in the number of vehicles worldwide, traffic congestion has been a problem in the field of transportation engineering that caused huge fuel consumption and traffic emissions [23]. it is known that delays caused by waiting at the stop-line of a signalized intersection may increase vehicles' fuel consumption and emissions.…”
Section: Fuel Consumptionmentioning
confidence: 99%
“…zhao et al [22] gave a cooperative speed advice and communication system called codrive to minimize fuel consumption at signalized intersections. fayazi and vahidi [23] proposed a controller-based modified mixed-integer linear programming at intersection for both autonomous and human-driven vehicles to improve signalized intersections time delay. in this work, we propose an algorithm and framework that guides cAvs on the mainline to create adequate gaps to the minor road that will eventually improve the flow of signalized intersections.…”
mentioning
confidence: 99%
“…They found that the ability to shape vehicle speed trajectories collaboratively plays a dominant role in reducing urban/suburban fuel consumption, while platooning plays a dominant role in influencing the attainable fuel savings on the highway. Zhao et al (Zhao et al, 2022) studied the fuel consumption of mixed traffic flow with CAV under three typical traffic scenarios (a basic segment with bottleneck zone, ramp of the freeway, and signalized intersection) based on the simulation platform of Python and SUMO. They found that the advantages of CAV are more evident at signalized intersections, and when the MPR of CAV is 100%, fuel consumption can be reduced by 32%.…”
Section: Introductionmentioning
confidence: 99%